Determination of Mg (II) in biodiesel by adsorptive stripping voltammetry at a mercury film electrode in the presence of sodium thiopentone - Zezza, Tina R. C. [UNESP] (2013)
A mercury film electrode was used to determine Mg (II) in biodiesel by adsorptive stripping voltammetry in presence of sodium thiopentone. A linear response was obtained for Mg (II) in the concentration range of 6.0 × 10-7 to 7.0 × 10-6 mol L-1 for SWAdSV and 8.0 × 10-7 to 9.0 × 10-6 mol L-1 for DPAdSV with detection limits of the 2.9 × 10-7 mol L-1 and 3.1 × 10-7 mol L-1, respectively. The method was applied successfully to biodiesel samples and presented goods results of accuracy with recoveries close to 100.0 % for SWAdSV and DPAdSV. © 2013 by ESG.